Beyond Utterances: Distributed Cognition as a Framework for Studying Discourse in Adults with Acquired Brain Injury - Duff, Melissa C.; Mutlu, Bilge; Byom, Lindsey; Turkstra, Lyn S. (Seminars in Speech and Language, 2012)
Considerable effort has been directed at understanding the nature of the communicative deficits observed in individuals with acquired brain injuries. Yet several theoretical, methodological, and clinical challenges remain. In this article, we examine distributed cognition as a framework for understanding interaction among communication partners, interaction of communication and cognition, and interaction with the environments and contexts of everyday language use. We review the basic principles of distributed cognition and the implications for applying this approach to the study of discourse in individuals with cognitive-communication disorders. We also review a range of protocols and findings from our research that highlight how the distributed cognition approach might offer a deeper understanding of communicative mechanisms and deficits in individuals with cognitive communication impairments. The advantages and implications of distributed cognition as a framework for studying discourse in adults with acquired brain injury are discussed.
Keywords: Distributed cognition; discourse; brain injury